The Relationship Between Functional Class of Heart Failure and Anxiety Level in Patient with Heart Failure - Febtrina, R (KnE Life Sciences, 2019)
Heart failure is a major health problem in the world as well as in Indonesia. Various sign and symptoms felt by patients with heart failure along with increasing degrees of heart failure can cause anxiety. The purpose of this study was to determine the relationship between the functional class of heart failure and the level of anxiety in patients with heart failure. This study used descriptive correlative method with cross sectional design. This study involved 50 respondents of heart failure patients. The instrument used to measure the functional class of heart failure was a questionnaire and the level of anxiety was assessed using DASS 21. Data analysis used chi square test. The results of this study showed that there is no a significant relationship between the functional class of heart failure and the level of anxiety (p value 0.55), so it can be concluded that the functional class of heart failure does not affect the level of anxiety in patients with heart failure. Recommendations from this study were nurses must provide nursing interventions to reduce the problem of anxiety in heart failure patients. Keywords: functional class of heart failure, anxiety, heart failure